Geometric dimensioning and tolerancing training program - Al Neumann (Geometric dimensioning and tolerancing, 1995)
Intended as training for anyone who interprets engineering drawings for manufacturing including manufacturing engineers, part designers, quality assurance inspectors and shop floor personnel.